Female Partners of Men with Peyronie's Disease Have Impaired Sexual Function, Satisfaction, and Mood, While Degree of Sexual Interference Is Associated with Worse Outcomes. Issue 7 (1st July 2016) - Davis, Seth N.P.; Ferrar, Saskia; Sadikaj, Gentiana; Gerard, Marina; Binik, Yitzchak M.; Carrier, Serge
ABSTRACT: Introduction: Peyronie's disease (PD) causes penile deformity and can result in sexual dysfunction and psychological distress. Currently, nothing is known about the psychosexual impact on the partners of men with PD. Research carried out on the partners of men with other chronic illnesses suggests that the partners of men with PD might have increased rates of sexual dysfunction and decreased sexual satisfaction. Aims: To examine (i) sexual functioning, sexual satisfaction, negative affect, and relationship satisfaction of men with PD and their female partners and (ii) the effect of male-perceived sexual interference on partners' outcomes. Methods: Forty-four men diagnosed with PD and their female partners completed a questionnaire package. Main Outcome Measures: Each partner filled out the Revised Dyadic Adjustment Scale, the Positive and Negative Affect Scale, the Global Measure of Sexual Satisfaction, and the Female Sexual Function Index (women) or the International Index of Erectile Function (men). Results: Overall, partners of men with PD were found to have decreased sexual function, sexual satisfaction, and mood compared with population-based norms. Men and their partners showed non-distressed levels of relationship satisfaction. The degree to which PD interfered with sexual activity was an important correlate of outcomes. Increased sexual interference was associated with lower sexual function and satisfaction for the person experiencing interference. Sexual interference also was associated with negative affect and relationship satisfaction in partners and the person experiencing interference. Conclusion: PD is associated with negative psychosexual and psychosocial effects on those with the disease and their partners. As a result, assessment and intervention should include the two members of the couple.